Blue Economy Positioning and Corporate Strategic Alignment: How Maritime Enterprises in the Global Industry Reconfigure Business Models Toward Sustainable Ocean Industries - Rosna Yuherlina Siahaan (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The Blue Economy — broadly defined as the sustainable use of ocean resources for economic growth, improved livelihoods, and ocean ecosystem health — has emerged as a transformative strategic framework reshaping how maritime enterprises conceptualize, design, and communicate their value propositions in global markets. This study investigates how global maritime enterprises strategically position themselves within the Blue Economy paradigm, examining the processes through which shipping companies, port operators, and maritime logistics organizations reconfigure their business models to align with sustainable ocean industry principles. Drawing on qualitative thematic analysis of thirty in-depth interviews with maritime C-suite executives, Blue Economy policy architects, sustainability strategists, and port development specialists, the research identifies four strategic positioning archetypes and three business model reconfiguration pathways. Findings reveal that successful Blue Economy alignment requires coherent integration of national maritime policy frameworks, stakeholder ecosystem management, and organizational capability reconfiguration — dimensions that individually insufficient Blue Economy strategies systematically neglect. The study advances maritime strategic management scholarship by providing an empirically grounded framework for Blue Economy corporate strategy in global maritime enterprises.